Challenges and best practices of managing government projects and programs - Kwak, Young-Hoon (Project Management Institute, Inc., 2014)
Drawing on an impressive array of large-scale government projects gleaned from government audit reports across three major sectors--infrastructure and transportation, information systems, and defense, this study explains why government projects go wrong and what can be done to improve their success rates. --